1976
DOI: 10.1111/j.1939-0025.1976.tb00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic factors in hyperkinesis: A critical evaluation.

Abstract: The role of organic factors in childhood hyperkinesis is evaluated, with a focus on electroencephalographic, neurological, biochemical, pregnancy and birth, and genetic research. Evidence that the majority of hyperkinetic children sufler from organic dysfunction is found to be minimal. This conclusion is discussed, and guidelines for future research are oflered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…3This research was approved by the University of Florida Human Subjects Committee. The ADI (Acceptable Daily Intake) level of FD&C Yellow #5 is 7.5 mg/kg (Noonan, 1972 (Dubey, 1976;Feingold, 1975aFeingold, , 1976Keogh, 1971;Knobel, 1962;Laufer and renhoff, 1957;Marwit and Stenner, 1972) …”
Section: Methodsmentioning
confidence: 99%
“…3This research was approved by the University of Florida Human Subjects Committee. The ADI (Acceptable Daily Intake) level of FD&C Yellow #5 is 7.5 mg/kg (Noonan, 1972 (Dubey, 1976;Feingold, 1975aFeingold, , 1976Keogh, 1971;Knobel, 1962;Laufer and renhoff, 1957;Marwit and Stenner, 1972) …”
Section: Methodsmentioning
confidence: 99%
“…Coleman (1971) and Rapaport, Quinn, Scribanu, & Murphy (1974) adopted the alternative strategy of measuring blood platelet serotonin levels in hyperactive and control children. Although Coleman did find low levels of platelet serotonin in the hyperactive group, these levels were not unlike those of nonhyperactive children who were undergoing stress (Dubey, 1976). Rapaport et al (1974) found no hyperactive vs. control differences and, further, found no connection between clinical response to drug therapy and serotonin levels.…”
Section: Critique Of Wender's Positioementioning
confidence: 96%
“…While some interesting research is going on in this area, it is important to note from the outset that no valid predictive index has yet been demonstrated (Barkley, 1976). As indicated above, a critical problem in this connection is that of objectively demonstrating that the drug has produced major effects (Dubey, 1976;McMahon & Greenberg, 1977). Another critical problem is that of finding sufficient numbers of children who perform in comparable ways on potential predictor variables.…”
Section: What Variables Predict Drug Effects?mentioning
confidence: 99%